Unraveling σ and π Effects on Magnetic Anisotropy in cis‐NiA4B2 Complexes: Magnetization, HF‐HFEPR Studies, First‐Principles Calculations, and Orbital Modeling1. Issue 47 (10th October 2016) - Charron, Gaëlle; Malkin, Elena; Rogez, Guillaume; Batchelor, Luke J.; Mazerat, Sandra; Guillot, Régis; Guihéry, Nathalie; Barra, Anne‐Laure; Mallah, Talal; Bolvin, Hélène
Abstract: By using complementary experimental techniques and first‐principles theoretical calculations, magnetic anisotropy in a series of five hexacoordinated nickel(II) complexes possessing a symmetry close to C 2 v, has been investigated. Four complexes have the general formula [Ni(bpy)X2 ] n + (bpy=2, 2′‐bipyridine; X2 =bpy (1 ), (NCS − )2 (2 ), C2 O4 2− (3 ), NO3 − (4 )). In the fifth complex, [Ni(HIM2 ‐py)2 (NO3 )] + (5 ; HIM2 ‐py=2‐(2‐pyridyl)‐4, 4, 5, 5‐tetramethyl‐4, 5‐dihydro‐1 H ‐imidazolyl‐1‐hydroxy), which was reported previously, the two bpy bidentate ligands were replaced by HIM2 ‐py. Analysis of the high‐field, high‐frequency electronic paramagnetic resonance (HF‐HFEPR) spectra and magnetization data leads to the determination of the spin Hamiltonian parameters. The D parameter, corresponding to the axial magnetic anisotropy, was negative (Ising type) for the five compounds and ranged from −1 to −10 cm −1 . First‐principles SO‐CASPT2 calculations have been performed to estimate these parameters and rationalize the experimental values. From calculations, the easy axis of magnetization is in two different directions for complexes2 and3, on one hand, and4 and5, on the other hand. A new method is proposed to calculate the g tensor for systems with S =1. The spin Hamiltonian parameters ( D (axial), E (rhombic), and g i ) are rationalized in terms of ordering of the 3 d orbitals. According to this orbital model, it can be shown that 1) the large magnetic anisotropy of4 and5 arises from splitting of the eg ‐like orbitals and is due to the difference in the σ‐donor strength of NO3 − and bpy or HIM2 ‐py, whereas the difference in anisotropy between the two compounds is due to splitting of the t2g ‐like orbitals; and 2) the anisotropy of complexes1 –3 arises from the small splitting of the t2g ‐like orbitals. The direction of the anisotropy axis can be rationalized by the proposed orbital model. Abstract : Seeking directions : In octahedral Ni II complexes, the interplay between the σ‐ and π‐donating capabilities of the ligands and their spatial orientation controls the ordering of the 3 d orbital energy in octahedral Ni II complexes, and thus, the magnitude and the nature of their magnetic anisotropy (see figure).